Comparing the effectiveness of different vaccination regimens using Sinovac and BNT162b2 vaccines among hospitalised patients: A single-centre hospital-based retrospective cohort study - Turan, Atakan; Öğüt, Hamdi; Ayyıldız Varol, Aylin; Koca, Nizameddin; Bozkurt, Hayri (The European Research Journal, 2025)
Objectives: This study aimed to assess the effectiveness of different vaccination regimens using two distinct SARS-CoV-2 vaccines against mortality risk and the need for intensive care unit (ICU) admission among hospitalised patients. Methods: The single-centre hospital-based retrospective cohort study was performed with adult COVID-19 patients in a tertiary-level hospital between March 2020 and September 2022. The associations between patients’ demographics and clinical features, vaccine status and regimens, in-hospital mortality, and need for ICU admission were evaluated using multivariable regression analyses. Results: During the study period, 2,373 patients were included. Mortality among unvaccinated patients was 85.0%, which was significantly lower in vaccinated groups (P